́Toma que o filme é teú: Sai de Baixo entre o teleteatro e a sitcom - de Oliveira, Édison Trombeta; Casado, Tiago Souza Machado [UNESP] (Universidade Estadual de Londrina, 2012)
A program recorded in a theater, with the audience, incorporating all of the improvisations and later televised. That was Sai de Baixo, TV Globos program broadcasted between 1996 and 2002. However, a specific episode limit this article. Toma 0que o filmeéteu, 1998, was made alive. Was it a spasm of the old teleplay Or was it just a common sitcom episode To answer these questions, the paper used a case study, bibliographical and documentary research and concluded that this episode was not a brief return of teleplay, having in mind that the fact of being alive is not a requirement to be teleplay, but there are other criteria.
You do it its your movie: Sai de baixo between teleplay and sitcom
Keywords: Sai de Baixo; Teleplay; Television genres